Pore-forming transmembrane domains control ion selectivity and selectivity filter conformation in the KirBac1.1 potassium channel - Matamoros, Marcos (J Gen Physiol, 2021)
Potassium (K(+)) channels are membrane proteins with the remarkable ability to very selectively conduct K(+) ions across the membrane. High-resolution structures have revealed that dehydrated K(+) ions permeate through the narrowest region of the pore, formed by the backbone carbonyls of the signature selectivity filter (SF) sequence TxGYG. However, the existence of nonselective channels with similar SF sequences, as well as effects of mutations in other regions on selectivity, suggest that the SF is not the sole determinant of selectivity. We changed the selectivity of the KirBac1.1 channel by introducing mutations at residue I131 in transmembrane helix 2 (TM2). These mutations increase Na(+) flux in the absence of K(+) and introduce significant proton conductance. Consistent with K(+) channel crystal structures, single-molecule FRET experiments show that the SF is conformationally constrained and stable in high-K(+) conditions but undergoes transitions to dilated low-FRET states in high-Na(+)/low-K(+) conditions. Relative to wild-type channels, I131M mutants exhibit marked shifts in the K(+) and Na(+) dependence of SF dynamics to higher K(+) and lower Na(+) concentrations. These results illuminate the role of I131, and potentially other structural elements outside the SF, in controlling ion selectivity, by suggesting that the physical interaction of these elements with the SF contributes to the relative stability of the constrained K(+)-induced SF configuration versus nonselective dilated conformations.